Implementasi Ketentuan Pasal 12 Peraturan Menteri Dalam Negeri Nomor 51 Tahun 2007 sebagai Dasar Pembentukan Kawasan Pertanian Terpadu - Sukriono, Didik (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to describe the determination of inter-village integrated growth centers based on Article 12 of the Minister of Home Affairs Regulation Number 51 of 2007 and analyze the formation of integrated agricultural areas based on the analysis of rural areas in the determination of inter-village integrated growth centers. This study used an empirical juridical method with a statutory and conceptual approach. The data in this study were obtained through observation, documentation, interviews, focus group discussions and conventional and electronic literature studies, which were analyzed using juridical qualitative methods. Determination of integrated growth centers between villages based on Article 12 of the Regulation of the Minister of Home Affairs Number 51 of 2007 was carried out by analyzing rural areas, both in terms of topography, natural resources, human resources, and facilities and infrastructure owned. The establishment of integrated agricultural areas based on the analysis of rural areas in determining the integrated growth centers between villages was carried out through four stages, namely the proposal of development plans, formulation of strategies and policies, planning of supporting programs, and legalization of integrated agricultural areas.